1986
DOI: 10.3109/02656738609019996
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intracellular pH induced by hyperthermia and hypoxia

Abstract: The effect of hyperthermia on pH of cells cultivated at varying pH of the medium and under different conditions of oxygenation has been studied. Chinese hamster fibroblasts and pig embryo kidney cells were used. The intracellular pH (pHi) was determined by the microfluorimetric method using fluorescein diacetate. The required temperature (37 degrees C and 41 degrees C) was maintained by a warm stage in combination with a thermochamber. Different conditions of oxygenation were achieved by placing the cells into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Chinese hamster fibroblasts and pig embryo cells have been used to study the effects of hyperthermia on intracellular pH using microfluorimetric methods 19 . To simulate conditions of oxygenation or hypoxia, pH i measurements were conducted in an open or closed cell incubation chamber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese hamster fibroblasts and pig embryo cells have been used to study the effects of hyperthermia on intracellular pH using microfluorimetric methods 19 . To simulate conditions of oxygenation or hypoxia, pH i measurements were conducted in an open or closed cell incubation chamber.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of hyperthermia (41degC) and hypoxia yielded a more intense acidification. Vexler and Litinskaya 19 concluded that hyperthermia stimulates glycolysis and, therefore, lactic acid production. This hypothesis is not supported by the present results.…”
Section: Discussionmentioning
confidence: 99%